Some Aspects of Eco Tourism with View to Montenegro: Overview - Jelisavka Bulatović; Goran Rajović (Centre for Behaviour and Wellness Advocacy, 2017)
The International Ecotourism Society defines ecotourism as responsible travel to natural areas that conserves the environment and sustains the well-being of local people (Honey, 1999). Thus, Ecotourism has been promoted as a non-consumptive use of nature and as a possible win - win development strategy, especially for underdeveloped areas. It should generate money in an ecologically and socially friendly way than other forms of land exploitation (Edwards et al., 1998). This article points to some aspects of eco-tourism, with emphasis on the Montenegro. The country has especially much to offer to nature enthusiasts.